1993
DOI: 10.14341/probl11906
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic composition of blood plasma carbon in patients with endocrine diseases

Abstract: достигнута у 7 (70%) больных, из оставшихся 3 больных у 2 отмечалось улучшение общего состояния, но уровень гормонов оставался повы шенным и у 1 больного в последующем была обнаружена кортиколиберинпродуцирующая опу холь легкого. В табл. 3 приведены результаты гормональных исследований у больных обеих групп после операции. Выводы 1. При болезни Иценко-Кушинга в диагности ческий комплекс в обязательном порядке должны быть включены КТ и ЯМРТ гипофиза.2. Методом выбора лечения при болезни Иценко-Кушинга, вызванно… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Further investigations demonstrated that isotope composition of different heterotrophs tissues has different composition that is pointed at isotope fractioning with metabolism. Investigations made by De Niro and Epstein [24], as well as Ivlev et al [3,4,25,26] were the most significant and informational for explanation of intramolecular fractioning of isotopes of carbon processes in heterotrophs organisms. Based on the undertaken studies, they made a conclusion: in every moment the cell is in particular functional state that corresponds to the given level of its energetic and biosynthetic needs that are controlled by regulatory connections system.…”
Section: Fractioning Of Carbon Isotopes In Biological Systems Of Livimentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigations demonstrated that isotope composition of different heterotrophs tissues has different composition that is pointed at isotope fractioning with metabolism. Investigations made by De Niro and Epstein [24], as well as Ivlev et al [3,4,25,26] were the most significant and informational for explanation of intramolecular fractioning of isotopes of carbon processes in heterotrophs organisms. Based on the undertaken studies, they made a conclusion: in every moment the cell is in particular functional state that corresponds to the given level of its energetic and biosynthetic needs that are controlled by regulatory connections system.…”
Section: Fractioning Of Carbon Isotopes In Biological Systems Of Livimentioning
confidence: 99%
“…Regarding the impact of natural isotopes concentrations on the living organisms' activity, including human beings, this point is still debating. The impact of daily biological rhythms on the human exhalation isotopic composition and the impact of pathologies of various etiologies on carbon isotopes composition in the blood can be mentioned [2][3][4][5][6][7]. Almost all the systems of the living body contain constant and natural radioactive isotopes, the nucleuses of which are different according to the number of criteria (weight, magnetic moment, quadrupole moment, spin).…”
Section: Introductionmentioning
confidence: 99%